Difussion of Inovation of Creative Industry Values on the Tenants of Sragen Tehcno Park Trough Business Incubator Model - Setiawan, Wawan Lulus; Indra, Nurhayat; Dewi, Lely Savitri (European Journal of Economics and Business Studies, 2017)
Currently creative industry in Indonesia is being develops as primary sector in economic development due to its capability to increase the value added of local resources, providing employment, and promoting tourism on the basis of sustainable development principles. Several techno park currently have been being developed by the government in various locations and various sector of economy as the focus of development. Sragen Tecno Park located in Central Java is one of Techno Park which focus on creative industry development trough business incubator model. In 2016 the program was followed by 10 (ten) new entrepreneurs as Tenants. By applying business incubator approach the Tenants were treated through the process beginning from selection, entrepreneurship training, managerial training, technical training, design and creativity training, as well as assistance, consulting, and advocating for marketing activities. Using the participatory action research, this qualitative study finds that business incubator model could improve creative industry values covering entrepreneurship values and art values of the Tenants, beside, supply chain and value chain of creative industry could be developed by the Tenant as well. This resulted in the improvement of business performance of the Tenant. Diffusion of innovation of creative industry values on the tenants trough business incubator model has indicated its effectiveness as an approach to develop Small and Medium Enterprises (SMEs), so that it has implication for policies of developing SMEs in other local resource based economic sector.